2007
DOI: 10.1557/mrs2007.192
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Deformation and Flow of Disordered Materials

Abstract: Disordered, glassy materials are arguably one of the least understood states of condensed matter. Yet, they are ubiquitous in everyday life (polymers, "soft" glasses such as toothpaste, various emulsions, pastes, and foams) and in demanding applications (metallic glasses). Much of what is known about this important class of materials has been the result of truly concerted experimental and molecular modeling efforts. It is now generally accepted that amorphous materials exhibit dynamic and mechanical heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…density in MGs and crystals of the same composition [38], whereas the almost systematically lower shear modulus of the MGs originates from the shear softening due to structural disorder. Specifically, the intrinsic non-affine elastic field [39] and the local anelastic deformation (relaxation) [40] have been demonstrated to be the microscopic characteristics of MGs under macroscopic elastic shear, in both experiments [41][42][43][44] and computer simulations [45][46][47][48][49][50][51][52], and proposed to be responsible for their reduced shear modulus [36,39,45,46]. These behaviors arise from the amorphous nature of the structure and its inherent fluctuation, as well as the resulting mechanical heterogeneity [53].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…density in MGs and crystals of the same composition [38], whereas the almost systematically lower shear modulus of the MGs originates from the shear softening due to structural disorder. Specifically, the intrinsic non-affine elastic field [39] and the local anelastic deformation (relaxation) [40] have been demonstrated to be the microscopic characteristics of MGs under macroscopic elastic shear, in both experiments [41][42][43][44] and computer simulations [45][46][47][48][49][50][51][52], and proposed to be responsible for their reduced shear modulus [36,39,45,46]. These behaviors arise from the amorphous nature of the structure and its inherent fluctuation, as well as the resulting mechanical heterogeneity [53].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Generically known as amorphous (or disordered) solids, they seem to have no more in common than what the etymology implies: their structure is disordered, that is to say, deprived of regular pattern at "any" scale, as liquids, but they are nonetheless solid. So heterogeneous a categorization may make one frown, but has proven useful in framing a unified theoretical description (Barrat and de Pablo, 2007). In fact, the absence of long range order or of a perceptible microstructure makes the steady-state flow of amorphous solids simpler, and much less dependent on the preparation and previous deformation history, than that of their crystalline counterparts.…”
mentioning
confidence: 99%
“…Recent experiments and numerical simulations work of Delogu, 17 Atzom, 18 and Egami [19][20][21] also demonstrate that when a glass subject to stress, which is much smaller than its normal yield strength, can also undergo an extremely slow flowing, which is hard to be detected within a short period of time due to the slowness. [17][18][19][20][21][22][23][24][25][26] Besides, the glass can even flow if the time is long enough (or the strain rate is small enough), which has been confirmed by experiments in the case of lower applied stress and temperature. [27][28][29] It is found that the microscopically localized flow in the apparent elastic regime of MG is markedly different from the stress-induced instantaneous flow of yielding and the subsequent plastic flow.…”
Section: Introductionmentioning
confidence: 72%